Analisis Kesalahan Berbahasa Indonesia: Kajian Morfologi Teks Drama Pada Kelas 8 SMP Muhammadiyah 3 Bandar Lampung - Sukma, Bibit; Salamah, Salamah; Idawati, Idawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study discusses morphological errors in drama texts with the aim of identifying errors in the use of language rules that are not in accordance with applicable language rules. The method used is descriptive qualitative research with data collection techniques in the form of reading, recording, and analyzing information. Based on the results of the study, 18 morphological errors were found in the drama text, including 4 suffixes, 5 prefixes, 2 confixes and 7 reduplicationsKeywords: Indonesian, Morphology, Drama Text